Ending the Civil War and Consequences for Congress - Finkelman, Paul; Kennon, Donald (Ohio University Press, 2019)
This collection explores the closing months and weeks of the Civil War and its implications for Congress in the postwar nation. Topics include ratification of the Fourteenth Amendment; Sherman's March and the laws of war; commemoration of the Civil War after 100 and 150 years; sectionalism, the Fourteenth Amendment, and the end of popular constitutionalism; treatment of federal prisoners of war; the refugee crisis at the end of the war and in the Reconstruction period; and the postbellum U.S. economy.